Pengaruh Lingkungan Kerja Dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Bidang Pemadam Kebakaran Dan Penyelamatan Kabupaten Pelalawan Provinsi Riau - Nurhayana, Nurhayana (Eko dan Bisnis: Riau Economic and Business Review, 2023)
This research aims to determine the influence of the work environment and organizational culture on employee performance in the fire and rescue sector in Pelalawan district, Riau province. The types of data used in this research are qualitative data and quantitative data. The population in this study was all 41 employees, the sample in this study was 41 employees or respondents. The data analysis technique uses the analytical assumption test, multiple linear regression analysis and statistical t test. Research data was collected from respondents and analyzed using linear regression and hypothesis testing. The results of this research show that the work environment has a positive and significant influence on employee performance, with a t-count value of (1.685 > 7.881) and organizational culture has a positive and significant influence on employee performance, with a t-count value of (1.685 > 3.119)